ASSESSMENT OF BONE MINERAL DENSITY IN NORMAL THAIS - POSHYACHINDA, Makumkrong; CHAIWATANARAT, Tawatchai (The ASEAN Journal of Radiology, 2023)
Bone mineral density (BMD) of anterior and lateral lumbar spine and femoral neck were studied in 301 normal healthy subjects (205 women and 96 men; age range, 20-84 years) utilizing dual energy x-ray absorptiometer (DEXA). In normal women, bone mass was increased with age and peaked around age 35 at all three scanning sites. Bone diminution began about the age of 40 and the loss was accelerated after age 50. The average rate of loss upto age 75 was 0.8% per year at all sites. In normal men, the pattern of bone diminution with age was different from women. Bone diminution from vertebrae and femoral neck began in young adulthood and were linear. The rate of decrease in BMD was two-thirds of that in women for femoral neck but was only one-fifth of that in women for anterior lumbar spine. Mean BMD in women was less than men at all three scanning sites.